The Implications of Unmet Need for Future Health Care Use: Findings for a Sample of Disabled Medicaid Beneficiaries in New York - Sharon K. Long; Jennifer King; Teresa A. Coughlin (SAGE Publishing, 2005)
Using survey data linked with Medicaid claims data, this study examines the consequences of unmet need for future health care use for a sample of disabled Medicaid beneficiaries in Westchester County, New York. Among other things, we find that individuals reporting unmet need in 1999 were more likely to use emergency room and hospital care in 2000 than those not reporting unmet need. Addressing the barriers to care that underlie unmet need could generate cost savings to Medicaid and provide better health outcomes for program beneficiaries.